A universal SARS‐CoV DNA vaccine inducing highly cross‐reactive neutralizing antibodies and T cells. Issue 10 (2nd September 2022) - Appelberg, Sofia; Ahlén, Gustaf; Yan, Jingyi; Nikouyan, Negin; Weber, Sofie; Larsson, Olivia; Höglund, Urban; Aleman, Soo; Weber, Friedemann; Perlhamre, Emma; Apro, Johanna; Gidlund, Eva‐Karin; et al.
Abstract: New variants in the SARS‐CoV‐2 pandemic are more contagious (Alpha/Delta), evade neutralizing antibodies (Beta), or both (Omicron). This poses a challenge in vaccine development according to WHO. We designed a more universal SARS‐CoV‐2 DNA vaccine containing receptor‐binding domain loops from the huCoV‐19/WH01, the Alpha, and the Beta variants, combined with the membrane and nucleoproteins. The vaccine induced spike antibodies crossreactive between huCoV‐19/WH01, Beta, and Delta spike proteins that neutralized huCoV‐19/WH01, Beta, Delta, and Omicron virus in vitro . The vaccine primed nucleoprotein‐specific T cells, unlike spike‐specific T cells, recognized Bat‐CoV sequences. The vaccine protected mice carrying the human ACE2 receptor against lethal infection with the SARS‐CoV‐2 Beta variant. Interestingly, priming of cross‐reactive nucleoprotein‐specific T cells alone was 60% protective, verifying observations from humans that T cells protect against lethal disease. This SARS‐CoV vaccine induces a uniquely broad and functional immunity that adds to currently used vaccines. Synopsis: This work describes the design and evaluation of a new type of genetic COVID‐19 vaccine, containing three binding domains from three SARS‐CoV‐2 variants combined with the M and the N proteins. The DNA vaccine induces high levels of broadly cross‐reactive and neutralizing antibodies to multiple SARS‐CoV‐2 variants. The vaccine primes broadly cross‐reactive T cells that even recognize Bat SARS‐COV sequences. The vaccine completely protects K18 mice from lethal disease caused by a challenge with the SARS‐CoV‐2 Beta variant. The data supports clinical data of this completely new DNA vaccine design. Abstract : This work describes the design and evaluation of a new type of genetic COVID‐19 vaccine, containing three binding domains from three SARS‐CoV‐2 variants combined with the M and the N proteins.